SONGS, DANCES, MIMES AND SYMBOLISM OF VENDA GIRLS' INITIATION SCHOOLS. A series of four articles in African Studies, Volume 28, Nos. 1-4, 1969, by Prof. John Blacking, University of the Witwatersrand, Johannesburg. Part 1. Vhusha; 2. Milayo; 3. Domba; 4. The Great Domba Song. Total pp. 186, 32 pp. ill., 12 pp. music. - Tracey, Andrew (International Library of African Music, 1970)
pages: 126-127
Keywords: African Music